Implementation of Lesson Study with Problem solving-Based Discovery Learning Model to Improve Mathematical Literacy Skills in SPLDV Class X Material - Lupita Sari, Muhammad; Andy Purnomo, Eko; Prihaswati, Martyana; Nurmawati, (Education, Science, and Technology International Conference, 2024)
This research aims to determine the implementation of lesson study with a discovery learning model based on problem solving in the System of Two Variable Linear Equations (SPLDV) material, increasing students' activeness and mathematical literacy skills and looking at student motivation. This research was carried out three times with the stages plan (planning), do (implementation), and see (reflection) at SMK PGRI 1 Taman, Pemalang Regency with the research subjects being class X TSM 3 students, totaling 36 students. This research uses a qualitative-quantitative approach where researchers collect qualitative data and quantitative data. Qualitative data was obtained in the form of documentation such as pictures during the learning process by implementing lesson study with a discovery learning model based on problem solving. The quantitative data obtained in this research were in the form of active observation sheets used by observers to observe students' activities during the learning process, test sheets for testing mathematical literacy abilities and student learning motivation questionnaires. The research results show that the learning process can run well, students can understand mathematics material. The test results of students' mathematical literacy skills and activeness can increase with each meeting and the average student motivation is in the sufficient category. Based on the research results, this research only discusses how to implement lesson study with a discovery learning model based on problem solving in the mathematics learning process. So that similar research regarding the implementation of lesson study with a discovery learning model based on problem solving can examine other learning processes.